High prevalence of retinal endothelial dysfunction in obesity WHO class III - Lammert, Alexander; Hasenberg, Till; Schnülle, Peter; Benck, Urs Tobias; Krämer, Bernhard; Hammes, Hans-Peter (Microvascular research, 2012)
Background: The extent of retinal endothelial dysfunction (ED) in patients with obesity is unknown. We evaluated markers of endothelial dysfunction to assess cardiovascular risk in patients with obesity WHO III° and their interrelation with classical cardiovascular risk factors. Methods: 120 patients (mean age 42.7±10.6years, 87 women) were prospectively evaluated for metabolic and cardiovascular risk using anthropometry, cardiovascular risk factors, lipid and glucose profiles. Intima media thickness (IMT) as marker of subclinical atherosclerosis, ED of retinal vessels, and the arteriole-to-venule ratio (AVR) of retinal vessels were assessed. Results: The mean BMI in our cohort was 48.7kg/m2. We diagnosed an overall prevalence of impaired glucose metabolism of 69.2%. 71.6% and 65.2% presented with arterial hypertension or dyslipidemia, respectively. Prevalences of retinal ED, pathologically reduced AVR, and enlarged IMT were 62.7%, 56.6% and 30%, respectively. Markers of endothelial function demonstrated correlation of neck to height ratio with dilatation of arteries (r=−0.333, p=0.01) and HDL cholesterol with dilatation of veins (r=−0.393, p=0.002). AVR was significantly related to neck circumference (r=−0.269, p=0.004). Conclusion: Retinal ED, AVR, and IMT as direct noninvasive surrogate measures of cardiovascular risk showed a high prevalence in patients with obesity WHO III°. We found no association of classical parameters for metabolic or cardiovascular risk with markers of endothelial dysfunction. Therefore, we have to hypothesize that other factors also play a pivotal role in the development of vascular pathology in patients with obesity.